EFFECT OF DIFFERENT CRYOPROTECTORS ON VIABILITY OF FROZEN-THAWED SPERMATOZOA OF BALKHASH PERCH (PERCA SHRENKII KESSLER, 1874) - Toishybek , D.Y.; Katubayeva , B.S.; Kumaeva , I.T.; Linnik , A.S.; Salmenova, M.Y.; Assanova , Y.A.; Toishibekov , Y.M.; Nurkenov , T.T. (Eurasian Journal of Applied Biotechnology, 2025)
In recent years, there has been active development of commercial aquaculture against the background of depletion of natural biological resources of water bodies, considering the growing need for food products. Cryopreservation of spermatozoa of rare and endangered fish species is of great importance, which will help preserve their biodiversity. Scientists are interested in perch as a potential commercial fish, but no studies have been conducted on cryopreservation of Balkhash perch spermatozoa. The Balkhash perch (Perca Shrenkii Kessler, 1874) is endemic to the Balkhash-Ili basin, and currently the population of this species is extremely low. In this study, work was carried out to determine the effect of various cryoprotectants on sperm motility before and after thawing for cryopreservation of Balkhash perch sperm. For this purpose, sperm from 10 males of this species was obtained and examined. During freezing, components of a protective solution were used with the addition of cryoprotectors glycerin and dimethyl sulfoxide to the sperm. The results of the study showed that before the addition of cryoprotectants, the motility was 74.3 ± 5.7%. Thawed samples frozen using the cryoprotectant 2.0 M glycerol retained motility significantly longer than those using 2.0 M dimethyl sulfoxide.